2021
DOI: 10.3390/ijms221910569
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Quantitative Detection Methods Based on Molecular Fluorescence Spectroscopy and Chromatographic Techniques Used for the Determination of Bisphenol Compounds

Abstract: Analytical methods using the fluorescence properties of bisphenols (BPA, BPF and BPS) and their complexes with β-cyclodextrin and methyl-β-cyclodextrin were developed. The methods were applied for the analysis of thermal paper and canned food. Their performance was compared with a standard HPLC approach with a diode array and fluorescence detections. For comparison purposes, basic validation parameters (linear range, limit of detection, sensitivity, precision) were evaluated. It was concluded the developed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Detection conditions were set based on fluorescent studies [ 26 ] for some of our analytes and our previous works [ 3 , 23 , 27 ]. For three analytes: BPF, BPE and BPA, the detector response is very similar.…”
Section: Resultsmentioning
confidence: 99%
“…Detection conditions were set based on fluorescent studies [ 26 ] for some of our analytes and our previous works [ 3 , 23 , 27 ]. For three analytes: BPF, BPE and BPA, the detector response is very similar.…”
Section: Resultsmentioning
confidence: 99%
“…The FLD enabled analysis across four different optimal wavelengths simultaneously, making it possible to obtain four different chromatograms and choose the most optimal one. Some bisphenols are described as a fluorescent molecules [34]. The bisphenols exhibited different fluorescent properties.…”
Section: Detection Conditionsmentioning
confidence: 99%
“…The detector responses for BPF and BPE were similar, and their structures differed only in the numbers of -CH 3 substituents attached to the carbon atom connecting the two phenyl rings. The FLD detector settings, such as excitation wavelength and emission wavelength, were selected based on a study of the fluorescence properties of BPA, BPS, and BPF [34]. Then, thanks to the possibility of measuring at four different excitation wavelengths with the FLD, four excitation wavelengths were selected (225, 230, 235, and 240 nm), while the emission wavelength was set to 300 nm during all analyses.…”
Section: Detection Conditionsmentioning
confidence: 99%
“…Orzel and Swit [31] compared quantitative detection methods based on molecular fluorescence spectroscopy and chromatographic techniques used for the determination of bisphenol compounds and concluded that high performance liquid chromatography with fluorescence detector (HPLC-FLD) result in the highest sensitivity and the lowest limit of detection (LODs) values. Due to similar spectral properties of BPA and BPF, simultaneous detection using the fluorescence approach is impossible [31]. This work supports our previous decision to use HPLC-FLD for the qualification and quantification of BPA migration from different packaging items and household products.…”
Section: Introductionmentioning
confidence: 99%